Design and evaluation of a maize monitoring system for precision planting - Yin, Yanxin; Chen, Liping; Meng, Zhijun; Li, Bin; Luo, Changhai; Fu, Weiqiang; Mei, Hebo; Qin, Wuchang (International Journal of Agricultural and Biological Engineering, 2018)
To increase the accuracy and real-time performance of on-line assessment of maize planting, a CAN bus based maize monitoring system for precision planting was designed and tested both in laboratory and field. The system was mainly comprised of: (a) seeding rate sensors based on opposite-type infrared photoelectric cell for counting the dropping seeds; (b) a decimeter GPS receiver for acquiring planter position and operation speed; (c) a vehicle monitoring terminal based on ARM Cotex-m4 core chip to acquire and process the whole-system data; (d) a touchscreen monitor to display the planter performance for the operator; and (e) a buzzer alarm to sound a warning when skip and double seeding happened. Taking the applicability, dependability and feasibility of the monitoring system into consideration, the opposite-type infrared photoelectric sensors were selected and their deployment strategies in the 6-port seed tube were analyzed. To decrease the average response time, a distributed information communication structure was adopted. In this information communication mode, collectors were designed for each individual sensor and communicated with sensors through two-wire CAN bus. A sensor together with the designed collector is called a sensor node, and each of them worked individually and took the responsibility for acquiring, processing, and transiting the on-going information. Laboratory test results showed that the random error distribution was approximately normal, and by liner analysis, the system observed value and the true value had as a liner relationship with coefficient of determination R2=0.9991. Series of field tests showed that the seeding rate maximum relative error of the 6-port seed tube was 2.92%, and the maximum root mean square error (RMSE) was about 1.64%. The monitoring system, including sensor nodes, vehicle monitoring terminal and a touch-screen monitor, was proved to be dependable and stable with more than 14 d of continuous experiments in field. Keywords: maize, precision planting, monitoring system, seeding rate, on-line assessment, CAN bus DOI: 10.25165/j.ijabe.20181104.3517 Citation: Yin Y X, Chen L P, Meng Z J, Li B, Luo C H, Fu W Q, et al. Design and test of precision seeding monitoring system for maize planter. Int J Agric & Biol Eng, 2018; 11(4): 186–192.